A Methodology to Conduct an End User Evaluation of Organisational Web Portal - Shely Mary Koshy; A. Sakeer Husain (Indian Journal of Extension Education, 2017)
An organization’s website being the face of an organisation requires a validated structure, easy for the virtual users to access it. The study showcases a methodology that can be utilized for finding how far the web portal is user friendly useful for a virtual user. A web interface developed for the Directorate of Research of Kerala Agricultural University was selected for the study. The web interface was evaluated considering its homepage, navigation, site organization, links and labels and readability. The organization of the web interface registered a high mean score of 3.90. The ’links and labels’, and the ’navigation’ also registered high mean scores of 3.89 and 3.87 respectively. The improvement was required in readability and appeal of the home page. This methodology clearly provides an insight to whether the developed site is user friendly and appealing thereby helps in the fine tuning of the organization’s websites/ interfaces.